TINJUAN YURIDIS TERHADAP PERATURAN MAHKAMAH AGUNG NOMOR 1 TAHUN 2016 TENTANG MEDIASI - Suryantoro, Dwi Dasa (Universitas Nurul Jadid, 2023)
PERMA Number 1 of 2016 concerning Procedures for Judicial Mediation is one of the factors that influence the effectiveness of mediation in court. The ratification of Regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number 1 of 2016 concerning Procedures for Mediation in the Courts has brought about fundamental changes in judicial practice in Indonesia. Mediation as an effort to reconcile disputing parties is not only important but must be carried out before a case is examined at trial. Peace efforts are not just a formality, but must be carried out seriously and sincerely to find a win-win solution to a problem for both parties so that they can find common ground. Settlement efforts do not only occur at the beginning of the trial, but throughout the discussion of the case and even at the end of the trial before the panel of judges announces its decision. According to PERMA Number 1 of 2016, mediation must be considered as one of the stages of the litigation process in the General Courts and Religious Courts.